Effectiveness of Vaccination Programs in Reducing Infectious Diseases - Reetika Kashyap (Oral Sphere Journal of Dental and Health Sciences, 2026)
Vaccinations are considered among the most effective ways to reduce the disease burden from infectious diseases in all regions of the world through public health interventions. Although there has been progress made in developing and strengthening the capacity of healthcare delivery systems, infectious diseases still account for a considerable number of cases of illness and death; this is especially true in low- and middle-income countries. This literature review will assess the efficacy of vaccines in preventing the transmission of infectious diseases and the influence of vaccines on public health. As well as significantly decreasing the incidence and mortality rates associated with infectious diseases such as measles, diphtheria and polio, vaccines can also help promote herd immunity by protecting populations with members who are immunocompromised or otherwise unable to obtain vaccinations. Unfortunately, vaccine refusal, misinformation about vaccines, logistics, and emerging pathogens create barriers that limit the ability of vaccination programs to achieve maximum effect. The literature review outlines these barriers and identifies possible solutions to increase access to vaccines, increase public confidence in vaccines, and ultimately enhance the overall effectiveness of vaccination programs. Furthermore, the literature review will highlight the socio-economic advantages of vaccination programs, including the cost-benefit analysis of how vaccines decrease the burden on healthcare systems and improve the quality of life of individuals. The literature review concludes that vaccination continues to be an essential component of global health security and requires continued evaluation, monitoring and adaptation in response to emerging threats to public health.